Kesenian Penthul Melikan Sebagai Sarana Pendidikan Karakter Bagi Anak di Dusun Melikan - Lisma Meilia Wijayanti; Nia Agustina (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to examine how Penthul Melikan art plays a role as a means of character education for children in Melikan Hamlet in Tempuran Village, Paron District, Ngawi. This study uses a descriptive qualitative approach to explore the role of Penthul Melikan art as a means of character education for children in Melikan Hamlet by involving children, coaches, and parents as subjects. Data were collected through participatory observation, in-depth interviews, visual documentation, and analyzed thematically by maintaining validity through triangulation and member checking. The researcher actively acted as the main instrument, maintaining ethics, local norms, and obtaining informed consent from all informants. The results of the study indicate that Penthul Melikan art plays a significant role as a means of character education for children in Melikan Hamlet. Through practice and performance, children naturally learn moral values ​​such as honesty, responsibility, cooperation, and empathy. Involvement in creative processes such as costume making and dialogue writing fosters discipline and a sense of responsibility. These values ​​are not only understood in the context of art, but also implemented in everyday life in a contextual and meaningful manner.